Navigating the Terrain of Sustainable Finance: A Phenomenological and Narrative Enquiry into Managerial Challenges - Al Owais, Abdelaziz; Joseph, Robinson (International Journal of Economics and Financial Issues, 2024)
This research aims to identify the managers’ perspective on implementing and adopting sustainable financing models in Dubai. Firstly, Sustainable financing must be defined to differentiate the sustainable model from the traditional financing models, secondly, provide past implementation practices to investigate both external and internal factors in comparison with traditional finance (TF). Finally, record the manager’s feelings around this topic. The methodology used is a primary qualitative to dig deeper into understanding from past literature and identify managerial participants from Dubai concerning the implementation of sustainable financing. The paper developed findings that defined the link or difference between sustainable financing (SF) and traditional finance (TF). The propositions in the qualitative literature from studies entail that the UN SGDs heavily influence sustainable financing to adopt ESG practices. However, greenwashing, high costs and ambiguity discourage investors and managers from integrating SF efficiently and indicate challenges to SF implementation. The study implies that the Sustainable Financing model is extremely like the traditional financing model except for the ESG compliance. However, regarding management and operations, the system does not differ much. It is evident that Sustainable Financing standardization is a challenge the managers face.